Clinical significance of a novel reticulocyte‐based erythropoietin resistance index in HD patients: A retrospective study. Issue 5 (12th December 2021) - Ueda, Eiko; Fujikawa, Tetsuya; Toya, Yoshiyuki; Kuji, Tadashi; Kakimoto‐Shino, Midori; Kawai, Yuki; Kawano, Tomoyuki; Azushima, Kengo; Wakui, Hiromichi; Tamura, Kouichi
Abstract: Introduction: The erythropoietin resistance index (ERI) is an indicator of erythropoiesis‐stimulating agent (ESA) responsiveness and is typically calculated using Hb. However, Hb does not directly reflect ESA‐induced erythropoiesis because of its long‐term nature. We thus designed a novel ERI calculated with reticulocyte Hb (RetHb), a real‐time index, and investigated its association with mortality in HD patients. Methods: We calculated the ERI using the change in RetHb before and after ESA administration (ERIΔRetHb ) and retrospectively analyzed its association with 3‐year all‐cause mortality using Kaplan–Meier survival curves and Cox regression analyses. Results: A total of 102 patients were included. Patients with the highest ERIΔRetHb had the worst prognosis according to the Kaplan–Meier survival curves (Log‐rank p = 0.02). Multivariate Cox regression analysis showed that the ERIΔRetHb was significantly and independently associated with all‐cause mortality (hazard ratio: 9.82, 95% CI [1.50, 64.41], p = 0.02). Conclusion: The ERIΔRetHb was significantly and independently associated with all‐cause mortality in HD patients.